2012
DOI: 10.1038/nature11251
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive prenatal measurement of the fetal genome

Abstract: The vast majority of prenatal genetic testing requires invasive sampling. Since this poses a risk to the fetus, one must make a decision that weighs the desire for genetic information against the risk of an adverse outcome due to hazards of the testing process. These issues are not required to be coupled, and it would be desirable to discover genetic information about the fetus without incurring a health risk. Here we demonstrate that it is possible to noninvasively sequence the entire prenatal genome. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
253
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(270 citation statements)
references
References 20 publications
(21 reference statements)
4
253
0
3
Order By: Relevance
“…The discovery of circulating cell‐free DNA (extracellular DNA; exDNA) and RNA (extracellular RNA; exRNA) in human body fluids, including serum, has sparked great interest in whether these molecules are functional, have regulatory effects, or can be used as markers of disease. For example, exDNA found in maternal serum has led to significant advancements in prenatal testing and diagnosis (Chiu & Lo, 2013; Fan, Blumenfeld, Chitkara, Hudgins & Quake, 2008; Fan et al., 2012; Lo et al., 1997), and for prediction of heart transplant rejection in adults (De Vlaminck et al., 2014; Snyder, Khush, Valantine & Quake, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The discovery of circulating cell‐free DNA (extracellular DNA; exDNA) and RNA (extracellular RNA; exRNA) in human body fluids, including serum, has sparked great interest in whether these molecules are functional, have regulatory effects, or can be used as markers of disease. For example, exDNA found in maternal serum has led to significant advancements in prenatal testing and diagnosis (Chiu & Lo, 2013; Fan, Blumenfeld, Chitkara, Hudgins & Quake, 2008; Fan et al., 2012; Lo et al., 1997), and for prediction of heart transplant rejection in adults (De Vlaminck et al., 2014; Snyder, Khush, Valantine & Quake, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The field is racing ahead: a flurry of papers, from Lo 2,3 , Stephen Quake at Stanford University in California 4,5 and genome scientist Jay Shendure at the University of Washington in Seattle 6 have honed the resolution with which scientists can analyse a fetal genome from tiny bits of DNA floating in the mother's blood. They can now count the number of chromosomes in a fetus 2,4 , and are developing ever-more-accurate ways to sequence genomes.…”
Section: Development Workmentioning
confidence: 99%
“…In addition, these tests are not highly sensitive or specific to detect trisomies (Lo, 2012). An exciting recent study by HC Fan and her colleagues sought to tackle this problem and showed that it is possible to non-invasively determine the entire genome of the fetus prenatally (Fan et al, 2012).…”
mentioning
confidence: 99%
“…However, the unique aspect of the study by Fan and colleagues is that, they demonstrated for the first time that acquiring the entire fetal genomic information is possible without having the paternal genetic map (Fan et al, 2012). This is extremely important in modern day world, where single parenthood and unknown paternity are common.…”
mentioning
confidence: 99%
See 1 more Smart Citation